Determining the Business Strategy of MSME Coffe Shops trough Financial Management and Recording Case Study of BDJ Shops - Rifki Khoirudin; Uswatun Khasanah; Suripto Suripto (UrbanGreen Central Media, 2022)
Weak understanding in managing cafe business finances is a fundamental problem for cafe businessmen at this time. In running cafe operations, cafe owners do not do good management and planning in using existing finances. This has caused many cafe businesses to go out of business or close due to improper planning, wrong financial management and operating expenses that are too high than income. This activity was carried out 4 times on 2 and 14 July and 5 and 12 October 2021. Financial management and regular recording of financial reports are important for business people, especially cafe entrepreneurs who are indeed large in terms of operations. The existence of financial management and routine financial records will provide an overview of the business being run, besides that it will also help provide decisions in planning future strategies for the cafe business. This service aims to provide an understanding of the importance of recording cafe business financial statements as the basis for financial management and making cafe business strategies in the future.